Stemness properties of SSEA-4+ subpopulation isolated from heterogenous Wharton’s jelly mesenchymal stem/stromal cells - Smolinska, Agnieszka; Chodkowska, Magdalena; Kominek, Agata; Janiec, Jakub; Piwocka, Katarzyna; Sulejczak, Dorota; Sarnowska, Anna (Frontiers in Cell and Developmental Biology, 2024)
Background: High heterogeneity of mesenchymal stem/stromal cells (MSCs) due to different degrees of differentiation of cell subpopulations poses a considerable challenge in preclinical studies. The cells at a pluripotent-like stage represent a stem cell population of interest for many researchers worldwide, which is worthy of identification, isolation, and functional characterization. In the current study, we asked whether Wharton’s jelly-derived MSCs (WJ-MSCs) which express stage-specific embryonic antigen-4 (SSEA-4) can be considered as a pluripotent-like stem cell population. Methods: SSEA-4 expression in different culture conditions was compared and the efficiency of two cell separation methods were assessed: Magnetic Activated Cell Sorting (MACS) and Fluorescence Activated Cell Sorting (FACS). After isolation, SSEA-4+ cells were analyzed for the following parameters: the maintenance of the SSEA-4 antigen expression after cell sorting, stem cell-related gene expression, proliferation potential, clonogenicity, secretome profiling, and the ability to form spheres under 3D culture conditions. Results: FACS allowed for the enrichment of SSEA-4+ cell content in the population that lasted for six passages after sorting. Despite the elevated expression of stemness-related genes, SSEA-4+ cells neither differed in their proliferation and clonogenicity potential from initial and negative populations nor exhibited pluripotent differentiation repertoire. SSEA-4+ cells were observed to form smaller spheroids and exhibited increased survival under 3D conditions. Conclusion: Despite the transient expression of stemness-related genes, our findings could not fully confirm the undifferentiated pluripotent-like nature of the SSEA-4+ WJ-MSC population cultured in vitro.